Analisis Efektivitas Pengumpulan Dana Zakat di Baznas Kabupaten Ciamis - Nisrina Athiyyah Nur Azizah; Fidhya Nurmalia; Dara Istia Aisyah; Elga Achmad Firdaus; Elis Nurhasanah (Islamic Economics and Business Review, 2024)
This research is entitled "Analysis of the Effectiveness of Collecting Zakat Funds in Baznas Ciamis Regency". Based on the title that the researcher took, this research has the main aim of finding out the effectiveness of the strategies and approaches used by BAZNAS Ciamis Regency in managing zakat funds, with the aim of improving the welfare of Muslims in Ciamis Regency. Ciamis region. This research is a type of qualitative descriptive research. The data collection techniques used were observation, interviews and documentation. Based on the research results, it was found that collecting zakat funds at BAZNAS was able to encourage public awareness and collaborate with village UPZs to collect zakat funds for ASN, as well as to entrepreneurs about the importance of zakat through education and outreach. The collection of zakat funds at BAZNAS Ciamis Regency has also been said to be effective as proven by the collection of zakat funds at the end of 2022 amounting to 17 billion from the initial target amount of only 13 billion.